Determination and evaluation of antioxidative activity in red dragon fruit (Hylocereus undatus) and green kiwi fruit (Actinidia deliciosa) - Halimoon, Normala; Abdul Hasan, Mardhiah Hayati (Science Publications, 2010)
Problem statement: Dragon fruit or pitahaya (Hylocereus undatus), is believed to be a healthy source of vitamins, fiber and antioxidants, especially the red-fleshed varieties which contain lycopene. Approach:Compared to green kiwi fruit (Actinidia deliciosa), which already known contain high antioxidant activity. Results:The antioxidant capacity of Hylocereus undatus (H. undatus) and Actinidia deliciosa (A. deliciosa) in three different solvent extraction; ethanol, methanol and aqueous, was estimated by DPPH free radical scavenging assay. The inhibition of free radical by A. deliciosa is almost 90% compared with H. undatus which only 60-10% in different solvents. Additionally, their total phenolic contents were analyzed by folin-ciocalteau method. The result showed that A. deliciosa (533.70 mg L-1 in ethanol, 460.87 mg L-1 in methanol and 420.652 mg L-1 in distilled water) seemed to be better sources of antioxidant compounds then H. undatus (179.35 mg L-1 in ethanol, 160.87 mg L-1 in methanol and 157.61 in distilled water). Conclusion: When compared between the three different solvent, extract in ethanol shown the most highly antioxidant content followed by methanol and water. The experiment showed the potential of dragon fruit and kiwi extracts high rich in antioxidant which can scavenge free radical in human body. Further study on isolation of individual antioxidant in both extracts can be providing for commercialize the extracts in jus form.